Differences in gut microbial diversity and composition between growth phenotypes of farmed juvenile sandfish, Holothuria scabra - Joselito A. Tabardillo; Marie Antonette Juinio-Meñez; Adam M. Reitzel; Rachel Ravago-Gotanco (BMC Microbiology)
Abstract Background The observed growth variability of different aquaculture species in captivity hinders its large-scale production. For the sandfish Holothuria scabra, a tropical sea cucumber species, there is a scarcity of information on its intestinal microbiota in relation to host growth, which could provide insights into the processes that affect growth and identify microorganisms with probiotic or biochemical potential that could improve current production strategies. To address this gap, this study used 16 S rRNA amplicon sequencing to characterize differences in gut and fecal microbiota among large and small juveniles reared in floating ocean nurseries. Results We recovered 5915 amplicon sequence variants and diversity indices revealed significant differences between large and small juveniles (p < 0.05). Gut microbiota of large juveniles had lower bacterial diversity than its smaller counterparts. The genus cluster Burkholderia-Caballeronia-Paraburkholderia (BCP) is the most common and abundant taxa found in the gut for both size categories but less abundant in fecal samples. Small juveniles had a higher abundance of members from the Roseobacter clade (Rhodobacteriaceae) such as Ruegeria, Shimia, Psuedoruegeria and Marivita among others while the genus Schlegelella (Caldimonas) and Bosea were primarily found in larger juveniles. Predicted physiological functions identified signatures of metabolism, biosynthesis, and biodegradation pathways unique for each size category. Significant differences in diversity and composition were also exhibited between the pooled fecal and gut sample types. Conclusions The bacterial composition in the intestinal tract of the sandfish H. scabra is an important factor in the observed growth variability in aquaculture. The results show differences in diversity, composition and predicted physiological functions between the size groups, despite being from the same cohort and environment. It was also evident that the fecal microbiota differs from the gut and does not correspond to size category, warranting caution in using the fecal matter as a proxy to infer microbial composition and interactions in the gastrointestinal tract. Understanding the roles that these microorganisms play in sandfish growth could support the development of strategies to manage size variation in captive-bred sea cucumbers, or for the promotion and selection for faster-growing individuals.